Efektivitas Program Anak Lahir Bawa Pulang Akta Di Dinas Kependudukan Dan Pencatatan Sipil Kota Palu - Magfira, Agra Daleta; Daswati; Muhammad Afandi (JPS: Journal of Publicness Studies, 2026)
The effectiveness of the Anak Lahir Bawa Pulang Akta program at the Department of Population and Civil Registration of Palu City. This study to determine the effectiveness of the Anak Lahir Bawa Pulang Akta program at the Department of Population and Civil Registration of Palu City. The research employs a qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data collection, data condensation, data presentation, and drawing conclusion. The result show that the implementation of the program has not been fully effective. The goal achievement indicator has not been optimally fulfilled, as evidenced by delays in the issuance of birth certificates. The obstacles include network disruptions and queues at partner health facilities, resulting in the the inability of families to receive the birth certificate when discharged from the facility. Moreover, the integration indicator has not been maximized, particularly in terms of outreach. Although the Department has made efforts to disseminate information to the public, especially to pregnant women community participation remains low. This indicates a gap between the implementation of socialization activities and public reception of the information. Overall, the effectiveness of the programs objective.